The Impact of Exclusive Breast Feeding on Infant Morbidity in The First Six Months of Infants Life - Maha A. Muhsen; Jabbar T. Ahmed (Institute of Medico-legal Publications Pvt Ltd, 2021)
The breast feeding was basic and ideal type of feed for infants especially during first six months of their life,breast feeding has a main role in infant’s life as maintaining on mental and physical health, protecting frommany disease and play important role in health of mothers and national and international strategies. Thegoals of this study is to estimate the prevalence exclusive breast feeding (EBF) in Basra (Southern of Iraq)during period of study, to determine the impact of exclusive breast feeding on morbidity of infant duringfirst six months of life and to assess relationship between some character’s for mothers and babies (Age ofmothers at marriage, Age of mothers at baby birth, educational level, occupation, birth interval, methodsof delivery, parity, gestational age, age, gender and birth weight of infant). The study found prevalence ofexclusive breast feeding in infants for first six months of life is 54.75%, while (23.75%) and (21.5%) forpartial and exclusive formula feeding respectively and showed significant relationship between diarrheadisease, respiratory tract infection and gastroenteritis and type of feeding in first six months of life at levelp<=0.05. also showed EBF associated with age of mothers at baby birth, education level, occupation ofmothers, and mode of delivery, gestational age and parity and found no relation between age of mothers atmarriage, birth interval and sex of infant with EBF.